2018
DOI: 10.1021/acscatal.7b04264
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic Water Splitting Using Al-Doped SrTiO3 Coloaded with Molybdenum Oxide and Rhodium–Chromium Oxide

Abstract: Al-doped SrTiO3 loaded with a rhodium–chromium mixed oxide (RhCrO x /STO:Al) efficiently promotes photocatalytic overall water splitting with an apparent quantum yield (AQY) of 56% under 365 nm ultraviolet (UV) light. Further increasing this AQY is of vital importance, because this value determines the maximum solar to hydrogen energy conversion efficiency that can be achieved. Herein, we demonstrate that the AQY during overall water splitting by RhCrO x /STO:Al is improved by 20% (to 69% at 365 nm) by coloadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
125
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(130 citation statements)
references
References 48 publications
3
125
0
2
Order By: Relevance
“…Therefore, modifications to SrTiO 3 are widely attempted to narrow the band-gap and thus enlarge its light-harvesting region. Chemical substitutional doping has been proposed as an effective method to modify SrTiO 3 [6], in order to obtain promoted photocatalytic activities, such as F-doped SrTiO 3 [7], Eu-doped SrTiO 3 [8], Al-doped SrTiO 3 [9], Cr-doped SrTiO 3 [10]. Among the abundant doped SrTiO 3 materials, Cr-doped SrTiO 3 exhibits variable properties caused by the suitable ionic radius of Cr 3+ (0.615 Å), which lies between those of Sr 2+ (1.18 Å) and Ti 4+ (0.605 Å) ions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, modifications to SrTiO 3 are widely attempted to narrow the band-gap and thus enlarge its light-harvesting region. Chemical substitutional doping has been proposed as an effective method to modify SrTiO 3 [6], in order to obtain promoted photocatalytic activities, such as F-doped SrTiO 3 [7], Eu-doped SrTiO 3 [8], Al-doped SrTiO 3 [9], Cr-doped SrTiO 3 [10]. Among the abundant doped SrTiO 3 materials, Cr-doped SrTiO 3 exhibits variable properties caused by the suitable ionic radius of Cr 3+ (0.615 Å), which lies between those of Sr 2+ (1.18 Å) and Ti 4+ (0.605 Å) ions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The result suggests that the degradation of the Rh 0.7 Cr 1.3 O 3 co‐catalyst is also progress beside the overall H 2 O splitting. According to the previous studies, the degradation of the Rh y Cr 2‐y O 3 co‐catalyst was reported to proceed by oxidizing Cr 3+ to Cr 6+ as chromate ion to dissolve in H 2 O. From the investigations in the previous study, under the oxidation process of H 2 O by photo‐generated holes, the degradation of the Rh 0.7 Cr 1.3 O 3 co‐catalyst also proceeds instead of production of O 2 .…”
Section: Influence Of Co‐catalysts To the Overall H2o Splitting Overmentioning
confidence: 95%
“…Recently, metal ion doped SrTiO 3 combined with a Rh y Cr 2‐y O 3 co‐catalyst was reported to show the excellent photocatalytic activity to the reaction. Particularly, Al ion doped SrTiO 3 prepared by the flux method exhibits extremely high photocatalytic activity under the irradiation of near‐UV region light that is containing the solar irradiation, where the apparent quantum yield is more than 50 % at 365 nm. A panel type reactor was made with using the photocatalyst and the overall H 2 O splitting was demonstrated under solar irradiation .…”
Section: Influence Of Co‐catalysts To the Overall H2o Splitting Overmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we report on the thermal annealing of SrTiO 3 (STO) nanocuboids, exhibiting highly ordered {110} and {001} facets. STO is an important material that can act as a substrate for the growth of high‐temperature superconducting thin films and plays a major role as a catalyst support and in photocatalysis . Understanding surface modifications of STO with temperature at the nanoscale is therefore extremely valuable to a wide range of industrial applications.…”
Section: Introductionmentioning
confidence: 99%